1997
DOI: 10.2307/3433605
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Information Systems: Their Use in Environmental Epidemiologic Research

Abstract: Advances ingorpicif id new oppo ntie r vm epi *0_|1 _. 1;**R~i... aifA.:..f:a. tra d 1 h4 aft...-iti~~~~~~~~~W hgdethe mapping of health data is not new to epidemiologists, advances in geographic information system (GIS) technology provide new opportunities for epidemiologists to study associations between environmental exposures and the spatial distribution of disease. In addition to the conduct of ecologic studies in which environmental exposure information is compared with disease rates across regions at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
1
9

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 5 publications
0
73
1
9
Order By: Relevance
“…Several of the reported limitations of using a GIS (Vine et al, 1997 ) apply to our study as well. The major problem was the availability of historic data.…”
Section: Application Of Gismentioning
confidence: 92%
See 2 more Smart Citations
“…Several of the reported limitations of using a GIS (Vine et al, 1997 ) apply to our study as well. The major problem was the availability of historic data.…”
Section: Application Of Gismentioning
confidence: 92%
“…Address geocoding based upon the six -position postal code was successful for 99.5% of the study population. For studies in the US, it has been reported that automated address matching was poor for rural areas (match rate of 20 -30% ) and much higher (98% ) for the largest urbanized county in North Carolina (Vine et al, 1997 ). A study in San Diego County reported a 85% address match, with missing data due in part to listing of PO boxes and incomplete addresses (English et al, 1999 ) .…”
Section: Application Of Gismentioning
confidence: 99%
See 1 more Smart Citation
“…For some tree pest control programs, records include mapped application areas, identification of specific pesticides used, and information about application rates and methods, whether aerial or ground -based. These records come closest to meeting the goals for GIS in health studies to include spatial, temporal, and intensity information (Vine et al, 1997 ). However, for many tree pest control activities, application areas could not be mapped within towns, or other information was missing.…”
Section: Discussionmentioning
confidence: 99%
“…Data are organized in ''coverages'' that include geographic information with an associated table of attributes. In health studies, spatial coordinates are linked with temporal and quantitative information representing the dates and levels of exposure (Vine et al, 1997 ). Coverages may be grouped together in one map as if they were transparencies layered on an overhead projector, and new maps may be created by manipulating multiple coverages and using algorithms to model environmental processes.…”
Section: Gis In Exposure Assessmentmentioning
confidence: 99%